2021
DOI: 10.3762/bjoc.17.121
|View full text |Cite
|
Sign up to set email alerts
|

Cerium-photocatalyzed aerobic oxidation of benzylic alcohols to aldehydes and ketones

Abstract: We have developed a cerium-photocatalyzed aerobic oxidation of primary and secondary benzylic alcohols to aldehydes and ketones using inexpensive CeCl3·7H2O as photocatalyst and air oxygen as the terminal oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
3
4
0
Order By: Relevance
“…It was proposed that chlorine radical (Cl˙) was responsible for the C(sp 3 )–H bond cleavage, 41–49 consistent with recent work from our group, where the generation of Cl˙ radicals was demonstrated as the rate-limiting step, and the Cl˙ reactivity could be altered by the addition of suitable additives (alcohols and arenes). 50 The oxygenation of gaseous alkanes ( i.e.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…It was proposed that chlorine radical (Cl˙) was responsible for the C(sp 3 )–H bond cleavage, 41–49 consistent with recent work from our group, where the generation of Cl˙ radicals was demonstrated as the rate-limiting step, and the Cl˙ reactivity could be altered by the addition of suitable additives (alcohols and arenes). 50 The oxygenation of gaseous alkanes ( i.e.…”
Section: Introductionsupporting
confidence: 77%
“…It was proposed that chlorine radical (Cl • ) was responsible for the C(sp 3 )-H bond cleavage, [41][42][43][44][45][46][47][48][49] consistent with recent work from our group, where the generation of Cl • radicals was demonstrated as the rate-limiting step, and the Cl • reactivity could be altered by the addition of suitable additives (alcohols and arenes). 50 The oxygenation of gaseous alkanes (i.e., CH 4 and C 2 H 6 ) mediated by [NEt 4 ] 2 [Ce IV Cl 6 ] was studied with the goal of transformation of light alkanes into liquid fuels under mild conditions, in contrast with ceria based catalysts that employ harsh conditions.…”
Section: Introductionsupporting
confidence: 71%
“…93 However, the Ce III photocatalysis has been thoroughly reviewed by Schelter elsewhere 94,95 and will not be covered here. Instead, we focus on the latest research on LMCT-enabled Ce IV photocatalysis, which has been led by Zuo, [96][97][98][99][100][101][102][103] Schelter, 104 König, [105][106][107] and Mashima 108, 109 over the past five years. Ce IV complexes are intrinsically powerful oxidants with redox potentials reaching as high as +1.63 V versus the standard calomel electrode for Ce(ClO4)3 under strongly acidic conditions.…”
Section: Zirconiummentioning
confidence: 99%
“…Besides, the fluorescence quenching experiments verified that the electron transfer occurred between the excited state of the POM and O 2 (Figure 4b), which was acoordance with the electron paramagnetic resonance (EPR) results (Figure S15) (EPR results demonstrated that the characteristic peaks of O 2 *À were observed under illumination, further confirming that O 2 *À was indeed formed during the reaction process). [54] Finally, no significant change in yield and selectivity was detected upon the addition of 2, 2, 6, 6-tetramethylpiperidine-N-oxyl (TEMPO) or isopropanol (IPA) to the reaction system, signifying 1 O 2 and OH * were not active species in this catalytic system. [55,56] Based on the literature reports and the above analysis, we proposed the mechanism of photocatalytic oxidation reaction of benzyl alcohol by compound 1 with the assitance of CAN and O 2 , [57][58][59][60] as shown in Scheme 1.…”
Section: Mechanistic Insights Into Benzyl Alcohol Oxidationmentioning
confidence: 96%